Identifying the burdens for informal caregivers of tracheostomy-dependent people: a scoping review protocol - Yuan Chu; Haiyan Luo; Xiao Miao; Song Liming (BMJ Open)
Introduction It is complicated and time-consuming to care for tracheostomised patients, and many informal caregivers are said to feel a variety of burdens, although we are unsure of the specifics of this burden. This scoping review aims to identify and examine the caregiver burden encountered by informal caregivers of patients with tracheostomy.Methods and analysis This scoping review will be carried out in accordance with Arksey and O’Malley and its extended framework, along with adherence to the guidelines provided by the Joanna Briggs Institute. Reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review checklists. Searches will be conducted in PubMed, PsycINFO via EBSCO, Embase, Web of Science and CINAHL via EBSCO databases, as well as grey literature sources from the inception of the databases to July 2024. Additionally, reference lists of included studies will be manually reviewed for further sources. The quality of included studies will be assessed using the Crowe Critical Appraisal Tool, involving at least two reviewers in all steps of the review process. Data charting will be conducted in a narrative format, encompassing the study’s objectives and questions. This review will also aim to identify any existing research gaps.Ethics and dissemination This review protocol does not involve ethical disclosure. This scoping review will identify the burden for informal caregivers of tracheostomy-dependent people and share the results via professional organisations, conferences and scholarly publications.Trial registration number This protocol was preregistered with the Open Science Framework (CENTER FOR OPEN SCIENCE), with Registration DOI (https://doi.org/10.17605/OSF.IO/YCWXR).